Pengembangan Buku Ajar IPAS Berbasis Literasi Sains Materi Bagian Tubuh Tumbuhan Kopi untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV SDN 2 Toyomarto Malang - Dwi Ayu Novitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to produce a valid, effective and practical science literacy based IPAS textbook in IPAS learning on the material of coffee plant body parts for grade IV students of SDN 2 Toyomarto Malang. The type of research used is Borg and Gall model R&D development research which consists of 10 stages, but researchers only use 8 stages, because at the 8th stage they can conclude the feasibility and effectiveness of the development product. The data collection methods used in this research were interviews, validation, tests, student responses and documentation. There are 3 data analysis techniques used, namely validity analysis through product validation score results from experts, effectiveness analysis and practicality analysis through student response questionnaires. The media validation results obtained a score of 89 in the very appropriate category, language validation obtained a score of 83.3 in the very appropriate category and material validation obtained a score of 92 in the very appropriate category. This effectiveness test was in the high effectiveness category with a result of 71.05% and the practicality results through the student response questionnaire obtained a percentage of 92.55% in the very practical category. The conclusion is that the science and science textbook is based on scientific literacy as material about the body parts of the coffee plant, valid, practical and effective for use in the learning process to improve learning outcomes
Reaploud Repository April 2026
Keywords: textbook; IPAS; science literacy; coffee plants